HUBUNGAN MOTIVASI BELAJAR DENGAN KETERAMPILAN MENULIS PUISI SISWA KELAS VIII SMP NEGERI 2 KECAMATAN SULIKI GUNUNG MAS - Sri Mures Walef (Menara Ilmu, 2019)
This research is motivated by several problems, namely (1) student learning motivation VIII SMP Negeri 2 Kecamatan Suliki Gunung Mas, (2) Students consider writing poetry is difficult and students do not pay attention to elements that build poetry, (3) motivation learning relationship with Poetry writing skills. The purpose of this study is, (1) to describe the students 'learning motivation, (2) to describe the students' poetry writing skills from the aspects of diction, image, and (3) to describe the relationship of learning motivation with students poetry writing skill.This research type is quantitative by using correlation method. The population in this study is the students of SMP Negeri 2 Kecamatan Suliki Gunung Mas amounted to 130 people consisting of 5 classes. Determination of the sample is done by cluster random sampling or randomly, then selected class VIII.3 which amounted to 26 students. Variables in this study is the motivation to learn as the variable X and skills of writing poetry as a variable Y. The instrument of this study is to distribute questionnaires and performance tests.Based on the results of the study can be concluded that the average value of learning motivation in general is 85 with good qualifications and the value of poetry writing skills is 80,23 with good qualifications. Furthermore, the correlation test using the moment product formula, obtained rhitung 0.1056, obtained t count 5,488 with degrees of freedom n-2 (26-2 = 24), and a significant level of 0.05. Hypothesis accepted if t count> t table. Thus H1 is accepted because the test results prove that t count is bigger than ttable that is 5,488 > 1,711. It can be concluded that there is a significant relationship between learning motivation and the skill of writing poetry of class VIII SMP Negeri 2 Suliki Gunung Mas. Kata kunci: motivasi belajar, keterampilan menulis, menulis puisi.